Spurious Prolongation of the Activated Partial Thromboplastin Time - Okpara, Robert A.; Carabello, Joann; James Day, H (Thrombosis and Haemostasis, 1977)
The clinical and laboratory data of 8 patients (4 males and 4 females) with circulating anticoagulant were presented. Based on prolonged APTT, failure to correct the APTT with 50 % normal plasma and abnormal tissue thromboplastin inhibition test, the inhibitor was identified as “middle stage” – or the “lupus anticoagulant”. Thrombokinetics showed the maximal rate of change in optical density (VmaxΔOD) of plasma, resulting from clot formation to be significantly less in the plasma of patients with the inhibitor than in normal plasma. This was not completely corrected by mixing the patients’ plasma with 50% normal plasma.